Comment on "A novel chaos based optical image encryption using fractional Fourier transform and DNA sequence operation". (June 2021) - Chen, Hang; Liu, Zhengjun; Tanougast, Camel; Blondel, Walter
Highlights: We have analyzed the image encryption scheme proposed by Farah et al. in a recent published article and point out its fatal weakness and design flaw of the optical system. Abstract: We numerically demonstrate that the optical image scheme using fractional Fourier transform and DNA sequence operation proposed recently by Farah et al. [Opt & Lasers Tech, 2020, 121: 105777] has the problem of using DNA xor operation and optical implementation. The original image cannot be decrypted completely accordingly to the inverse encryption process.